Ocorrência de anormalidades nos seios maxilares detectadas por meio da tomografia computadorizada por feixe cônico (TCFC) em pacientes assintomáticos - REGE, Inara Carneiro Costa (2011)
The use of cone beam computed tomography exam (CBCT) has increased greatly in recent years in dentistry, so there is much discussion about the role of the dentist in evaluating the anatomical structures near the maxillo-mandibular. Currently we do not know the occurrence of abnormalities in the maxillary sinuses in a large sample of CBCT examinations of dental patients with different indications. The aim of this study was 1-to investigate the occurrence of maxillary sinus abnormalities using cone beam computed tomography (CBCT) exams of asymptomatic patients, 2- identify the frequency, type and location of these findings, and 3- its association with the proximity of periapical lesions and inflammatory changes in the maxillary sinus.1113 CBCT exams were evaluated by two examiners to identify the presence or absence of abnormalities of the maxillary sinus. Cases with abnormalities were reevaluated for identification of the type of the abnormality and location within the sinus. The presence and proximity of periapical lesions in the upper posterior teeth to the lower sinus wall were recorded. Data were analyzed using descriptive statistics and chi-square test. Inter-rater agreement was calculated using Kappa statistics. Abnormalities were diagnosed in 760 (68.2%) cases (kappa coefficient 0.83). There was a significant difference between genders, showing greater occurrence in males (p<0.001). No difference in the occurrence of abnormalities was observed regarding age groups (p>0.05). Mucosal thickening was the most prevalent abnormality (66%), followed by retention cyst (10.1%) and opacification (7.8%). The most frequent location of sinusal abnormalities were in the inferior wall (46.2%), anterior (29%), medial(25.7%) and lateral wall (21.5%). No association between the proximity of periapical lesion and the presence and type of inflammatory abnormalities was observed (p=0.124). The occurrence of abnormalities in maxillary sinus of asymptomatic was considered high. These findings emphasize the importance of a comprehensive interpretation by the dentomaxillofacial radiologist of all volume of CBCT images, including the entire maxillary sinus as part of the imaging exam of routine patients.